Hydration and diffusion processes shape microbial community organization and function in model soil aggregates. Issue 12 (19th December 2015) - Ebrahimi, Ali; Or, Dani
Abstract: The constantly changing soil hydration status affects gas and nutrient diffusion through soil pores and thus the functioning of soil microbial communities. The conditions within soil aggregates are of particular interest due to limitations to oxygen diffusion into their core, and the presence of organic carbon often acting as binding agent. We developed a model for microbial life in simulated soil aggregates comprising of 3‐D angular pore network model (APNM) that mimics soil hydraulic and transport properties. Within these APNM, we introduced individual motile (flagellated) microbial cells with different physiological traits that grow, disperse, and respond to local nutrients and oxygen concentrations. The model quantifies the dynamics and spatial extent of anoxic regions that vary with hydration conditions, and their role in shaping microbial community size and activity and the spatial (self) segregation of anaerobes and aerobes. Internal carbon source and opposing diffusion directions of oxygen and carbon within an aggregate were essential to emergence of stable coexistence of aerobic and anaerobic communities (anaerobes become extinct when carbon sources are external). The model illustrates a range of hydration conditions that promote or suppress denitrification or decomposition of organic matter and thus affect soil GHG emissions. Model predictions of CO2 and N2 O production rates were in good agreement with limited experimental data. These limited tests support the dynamic modeling approach whereby microbial community size, composition, and spatial arrangement emerge from internal interactions within soil aggregates. The upscaling of the results to a population of aggregates of different sizes embedded in a soil profile is underway. Key Points: Dynamics of hydration influence the composition and function of microbial community The conditions in soil aggregates are of particular interest due to limitations to oxygen diffusion Anoxic region in aggregates shapes the self‐organization of aerobic and anaerobic communities